Evaluation of efficacy and safety of generic tacrolimus (Suprotac®) compared to reference tacrolimus (Prograf®) in kidney transplantation: a phase IV study - Behzad Einollahi; Mohsen Nafar; Mohammad Javanbakht; Amirhesam Alirezaei; Jalal Azmandian; Abbas Etminan; Mohammad Reza Ardalan; Jalal Etemadi; Roghayeh Akbari; Vahid Pourfarziani; Seyed Sadraddin Rasi Hashemi; Seyed Maryam Rahbar; et al. (European Journal of Translational Myology)
Background